Relative Telomere Length and Cardiovascular Risk Factors - Moritz Koriath; Christian Müller; Norbert Pfeiffer; Stefan Nickels; Manfred Beutel; Irene Schmidtmann; Steffen Rapp; Thomas Münzel; Dirk Westermann; Mahir Karakas; Philipp S. Wild; Karl J. Lackner; et al. (Biomolecules, 2019)
(1) Background: Telomeres are repetitive DNA sequences located at the extremities of chromosomes that maintain genetic stability. Telomere biology is relevant to several human disorders and diseases, specifically cardiovascular disease. To better understand the link between cardiovascular disease and telomere length, we studied the effect of relative telomere length (RTL) on cardiovascular risk factors in a large population-based sample. (2) Methods: RTL was measured by a real-time quantitative polymerase chain reaction in subjects of the population-based Gutenberg Health Study (n = 4944). We then performed an association study of RTL with known cardiovascular risk factors of smoking status as well as systolic and diastolic blood pressure, body mass index (BMI), LDL cholesterol, HDL cholesterol, and triglycerides. (3) Results: A significant correlation was shown for RTL, with age as a quality control in our study (effect = −0.004, p = 3.2 × 10−47). Analysis of the relation between RTL and cardiovascular risk factors showed a significant association of RTL in patients who were current smokers (effect = −0.016, p = 0.048). No significant associations with RTL were seen for cardiovascular risk factors of LDL cholesterol (p = 0.127), HDL cholesterol (p = 0.713), triglycerides (p = 0.359), smoking (p = 0.328), diastolic blood pressure (p = 0.615), systolic blood pressure (p = 0.949), or BMI (p = 0.903). In a subsequent analysis, we calculated the tertiles of RTL. No significant difference across RTL tertiles was detectable for BMI, blood pressure, lipid levels, or smoking status. Finally, we studied the association of RTL and cardiovascular risk factors stratified by tertiles of age. We found a significant association of RTL and LDL cholesterol in the oldest tertile of age (effect = 0.0004, p = 0.006). (4) Conclusions: We determined the association of relative telomere length and cardiovascular risk factors in a population setting. An association of telomere length with age, current smoking status, as well as with LDL cholesterol in the oldest tertile of age was found, whereas no associations were observed between telomere length and triglycerides, HDL cholesterol, blood pressure, or BMI.